Case Report: Idiopathic Spinal Cord Herniation: An Overlooked and Frequently Misdiagnosed Entity - Yang, Chenlong; Lin, Guozhong; Zhang, Jia; Yang, Jun; Xie, Jingcheng (Frontiers in Surgery, 2022)
Background: Idiopathic spinal cord herniation is an extremely rare entity that is characterized by protrusion of the spinal cord through a defect in the ventral dura. Due to the paucity of enough clinical evidence, the treatment and prognosis of idiopathic spinal cord herniation are still elusive. Herein, we reported a case of idiopathic spinal cord herniation occurring at the C7–T1 levels that was treated by surgical reduction. Case description: A 44-year-old Chinese woman presented with a 5-year history of numbness and weakness in the bilateral lower limbs. Spinal magnetic resonance imaging demonstrated ventral displacement of the spinal cord at the C7–T1 levels, and there seemed to be a cuneiform space-occupying lesion dorsal to the spinal cord. A diagnosis of the spinal intradural extramedullary tumor was suspected. An exploratory operation was performed via a posterior midline approach. Intraoperatively, we found a defect in the ventral dura through which the spinal cord herniated to the epidural space. After the herniated parenchyma was returned, an artificial dura matter was used to repair the defect. The postoperative course was uneventful. After a 3-month follow-up, the lower-extremity weakness was significantly improved, and there was no recurrence of the spinal cord herniation. Conclusion: Preoperative diagnosis of idiopathic spinal cord herniation is exceedingly challenging. Surgical reduction of the herniated spinal cord with the repair of the dural defect is an effective approach for the treatment of this rare disorder, and the surgical outcome is favorable.